Upaya Dalam Menangani Korban Kekerasan Seksual Pada Anak (Studi Pada Dinas Pemberdayaan Perempuan Perlindungan Anak dan Pengendalian Penduduk Keluarga Berencana Kabupaten Pelalawan) - Wilis Hestiningsih; Riky Novarizal (SISI LAIN REALITA, 2020)
This research purpose is to know kriminogen factor that cause of criminal action sexual violence of children of Pelalawan Regency and to knows hpw does the effort of woman and children department and inhabitant control planed family in cope with criminal action sexual violence of children at Pelalawan Regency. This research is descriptive empirical. The date uses is primer date interview and secunder date through book. Collection technique is from study case and literature study. Analyst date technique did by used, collective, and selection date from thr study case add connecting by the theory and principle with law of norin from literature study. Based from the research result shows that effort to take in halde sexual violence of children can do as SOP that unchanged it strated from society complaint, reaching victims, management case, temporary collecting, mediation, accompanying victims and evaluation activity towards sub district and lillages in Pelalawan Regency. The effectiveness of this effort gave to the sexual violence of children at Pelalawan Regency was not effective yet,so that needed social awareness to words sexual violence of children.